The dynamics of the development of canang kayu musical instruments in the Aceh Singkil community - Purba, Junaidi; Sebayang, Vanesia Amelia; Hennywaty, Yusnizar (International Journal of Culture and Art Studies, 2025)
This study discusses the dynamics of the development of canang kayu musical instruments in the Aceh Singkil community. Canang kayu, which initially served as a traditional musical instrument in rituals and religious activities, has undergone changes in form, function, and context of use over time. Using a descriptive qualitative approach through observation, interviews, and documentation, this study was analyzed based on Herkovits’ Theory of Change. The results of the study indicate that the Canang Kayu musical instrument has undergone changes in its aesthetic subjects, objects, and ethics. These changes can be seen in the number of notes and in the player’s position at formal events and traditional ceremonies. Despite the changes, Canang Kayu continues to uphold the values of local culture and the identity of the Aceh Singkil community.